INVENTARISASI JENIS PAKAN MONYET HITAM SULAWESI (Macaca nigra) DI SUAKA MARGASATWA MANEMBO-NEMBO - Olivia S. M. Turangan; Hard N. Pollo; Johny S. Tasirin (COCOS, 2022)
ABSTRAK The threat to Macaca nigra is due to the increasing number of hunting by humans and the destruction of natural habitats that occur. Macaca nigra is hunted for consumption, trade and as pets for the community. The reduction in forest area causes Macaca nigra to lack shelter and food sources. The purpose of this study was to make an inventory of Macaca nigra feed in the Manembo-nembo Wildlife Sanctuary. The method used at the research location is the Transect Method (Line). Observations began by observing the home range of a group of Macaca nigra to place the plot line to be made. Based on the results obtained from the results of research conducted at the Manembo-nembo Wildlife Sanctuary, the number of types of feed found was 27 species from 15 families with 188 individuals. The highest number of individuals, 83 individuals, was from the Arecaceae family, and the lowest number of individuals, 1 individual, was from the Anacardiaceae and Malvaceae families